Critical discourses on resilience: exploring alternatives strategies used by young people at-risk - Pessoa, Gomes A. S. [UNESP] (2014)
The concept of resilience is often situated in a dominant discourse that reflects medical and developmentalist epistemology, in Western models, with the ideology of white people, and middle class hegemonic norms. Behavior that falls outside of the normal, or what is socially acceptable, is associated with riskiness and tacitly if not explicitly labeled as pathological, and then, not resilient. However, the context of social injustice of many young people at-risk can have drastic effects on them. When we offer institutions such as schools that do not understand their needs, they may refuse our services and some of them may engage in antisocial activities, since they are looking for personal validation, pathways to recognize themselves, and places and organizations that contribute to the building of their social identity. This paper analyses how the denial of support and resources for the wellbeing of young people can lead them to situations that are socially unacceptable, such as sexual exploitation and drug trafficking. The main argument is that these activities, in the absence of conventional mechanisms, may bring some benefit to the subjects. Benefits may be in material conditions, though strongly marked by issues of social inequality; or subjective, in gaining relationships with people outside the normative places and institutions for young people. Unconventional circumstances produce unconventional attitudes that are expressed in alternative forms of resilience.